Solid waste-based anti-seepage material as well as preparation method and application thereof

By optimizing the ratio and preparation method of solid waste-based concrete, solid waste-based anti-seepage materials composed of coal gangue, blast furnace slag, lithium slag, alkali slag and modifiers are used to solve the problem of poor anti-seepage effect of heavy metals in lithium slag yards, and achieve more efficient environmental protection and resource utilization.

CN119874235APending Publication Date: 2025-04-25GUIZHOU DEEP CARBON TECH CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510087396.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing solid waste-based concrete has poor anti-seepage effect of heavy metals in lithium slag yards, and there are problems of high cost and poor durability.

Method used

The solid waste-based anti-seepage material consisting of coal gangue, blast furnace slag, lithium slag, alkali slag and modifier is used to improve the heavy metal anti-seepage performance of the material through optimized proportion and preparation methods.

Benefits of technology

It significantly improves the anti-seepage effect of heavy metals in the lithium slag yard, reduces the impact on the surrounding and groundwater environment, and reduces production costs and carbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874235A_ABST
    Figure CN119874235A_ABST
Patent Text Reader

Abstract

The invention discloses a solid-waste-based anti-seepage material as well as a preparation method and application thereof. The solid-waste-based anti-seepage material comprises the following components in parts by mass: 40-45 parts of coal gangue, 20-30 parts of blast furnace slag, 20-25 parts of lithium slag, 10-20 parts of alkaline residue and 5-10 parts of a modifier, through cooperation and modification of all the components, the anti-seepage effect on heavy metal percolation of the lithium slag storage yard is good, durability is good, and the influence on the surrounding and underground water environment can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid waste treatment, and in particular to a solid waste-based anti-seepage material and a preparation method and application thereof. Background Art

[0002] Lithium carbonate is the main raw material for new energy batteries. On average, 30-50 tons of lithium slag are produced for every ton of lithium carbonate produced. The comprehensive utilization of lithium slag is urgent. Lithium slag contains a variety of heavy metals and harmful substances. The heavy metals that need to be prevented from leaching are beryllium Be and thallium Tl. If not handled properly, they will cause serious pollution to the environment. Therefore, effective anti-seepage measures are needed for lithium slag yards to prevent harmful substances from seeping into the soil and groundwater.

[0003] The anti-seepage cushion layer is a key barrier to prevent the migration of harmful substances. Traditional anti-seepage materials may have problems such as high cost and poor durability. The use of solid waste-based concrete as an anti-seepage cushion layer can improve its durability and stability, while realizing the resource utilization of solid waste; however, the current effect of using solid waste-based concrete to prevent heavy metal seepage in landfills needs to be further improved.

[0004] Therefore, it is necessary to provide a solution with good heavy metal seepage prevention effect on lithium slag yard. Summary of the invention

[0005] In view of the defects in the prior art, the present invention proposes a solid waste-based anti-seepage material and a preparation method and application thereof, so as to solve the problem of how to improve the heavy metal anti-seepage effect of solid waste-based cementitious materials.

[0006] In order to solve the above technical problems, this application provides the following technical solutions:

[0007] In a first aspect, the present application provides a solid waste-based anti-seepage material, comprising the following components in parts by weight: 40-45 parts of coal gangue, 20-30 parts of blast furnace slag, 20-25 parts of lithium slag, 10-20 parts of alkali slag, and 5-10 parts of modifier.

[0008] Preferably, the modifier comprises a mixture of polyferric sulfate and nano-silicon dioxide in a mass ratio of 1:(1-2).

[0009] Preferably, the particle size of coal gangue is 0.18-0.25 mm, the particle size of blast furnace slag is 10-75 μm, the particle size of alkali slag is 0.15-0.25 mm, and the particle size of lithium slag is 37-74 μm.

[0010] Preferably, in the blast furnace slag, the molar ratio of calcium to silicon is ≤0.6, the molar ratio of aluminum to silicon is ≥0.15, and the molar ratio of calcium to the sum of silicon and aluminum is ≤1.3.

[0011] In the second aspect, the present application provides a method for preparing a solid waste-based anti-seepage material, comprising the following steps: mixing coal gangue, lithium slag, alkali slag, and blast furnace slag that have been ball-milled and dried according to mass parts, and then adding water, heating and stirring to obtain a mixture; adding a modifier to the mixture, carrying out a modification reaction, and obtaining a solid waste-based anti-seepage material.

[0012] Preferably, the heating and stirring process includes a first heating reaction and a second heating reaction; the final temperature of the first heating reaction is 60-70°C, the duration is 18-30h, and the heating rate is 1-2°C / h; the final temperature of the second heating reaction is 90-100°C, the duration is 6-12h, and the heating rate is 4-5°C / h.

[0013] Preferably, the pH value of the heating and stirring is 10-12.

[0014] Preferably, the pH value of the modification reaction is 5-7.

[0015] In a third aspect, the present application provides a solid waste-based anti-seepage material for use as a geopolymer.

[0016] Preferably, the application method comprises mixing the solid waste-based anti-seepage material, hydrotalcite and piezoelectric catalyst and then landfilling.

[0017] In summary, compared with the prior art, the present invention achieves the following technical effects: the solution provided by the present invention has a good anti-seepage effect on heavy metals in lithium slag yards, and can reduce the impact on the surrounding and groundwater environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 SEM images of different materials. DETAILED DESCRIPTION

[0019] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0020] Gangue is solid waste generated during coal mining and washing. Its utilization can reduce resource waste and environmental pollution. Gangue can be used as aggregate and admixture for concrete. Through specific proportions and preparation methods, it can be made into gangue concrete with excellent performance. Blast furnace slag is a by-product of the steel industry. It is rich in silicates and aluminates and has potential hydraulic activity. Lithium slag has volcanic ash activity and can be used as an admixture for concrete and mortar to replace part of the cement and realize resource utilization. Alkali slag is solid waste generated by the chemical industry. It contains a large amount of alkaline substances and is harmful to the environment. By combining it with concrete materials, its impact on the environment can be reduced while improving the performance of concrete.

[0021] By optimizing the proportion of solid waste-based cementitious materials and realizing the full-component optimization control technology, the production cost can be greatly reduced, and the production cost of solid waste-based cementitious materials can be reduced by 50% compared with ordinary Portland cement, and carbon emissions can be reduced by 90%. The application of solid waste-based anti-seepage layer can not only prevent the seepage problem of heavy metals in the yard, but also absorb industrial solid waste, reduce the cost of using anti-seepage cushion layer in lithium slag yard, and achieve the purpose of treating harm with waste.

[0022] Based on this, this application was created.

[0023] The present application provides a solid waste-based anti-seepage material, comprising the following components in parts by mass: 40-45 parts of coal gangue, 20-30 parts of blast furnace slag, 20-25 parts of lithium slag, 10-20 parts of alkali slag, and 5-10 parts of a modifier.

[0024] The raw materials in this application cooperate with each other to achieve anti-seepage effect, and the mechanism is as follows:

[0025] The adsorbent materials such as pyrite contained in coal gangue can react with the alkaline substances (such as OH -) react to form an alkaline environment. On the one hand, the alkaline environment helps to neutralize acidic substances and reduce the erosion of acidic substances on concrete structures to improve the durability of solid waste-based anti-seepage materials, while enhancing the adsorption capacity for heavy metal ions; on the other hand, the alkaline environment formed can also promote the activity of certain components in coal gangue and improve its hydration reaction efficiency in concrete. When the hydration reaction efficiency is high, more hydration products such as hydrated calcium silicate (CSH), hydrated calcium aluminosilicate (CASH), and calcium sulfonate will be generated. These hydration products have a high specific surface area and a porous structure, which can provide a large number of adsorption sites and have a strong adsorption capacity for heavy metal ions (such as beryllium, thallium, etc.), thereby reducing their mobility. For example, the solidification mechanism of thallium is not only reflected in its fixation in calcium sulfonate by forming thallium sulfate, but also in the enhancement of the stability of the crystal by supplementing the charge. In addition, thallium ions can form covalent bonds with aluminum oxide tetrahedrons in calcium aluminosilicate hydrate (CASH). This chemical bonding can improve the chemical stability of the material and significantly enhance the fixation effect on thallium ions. Efficient hydration reactions can fill the pores inside the material to form a denser structure. The dense structure not only improves the material's impermeability, but also reduces the path of heavy metal leachate through the material, significantly enhancing the anti-seepage effect. In addition, the efficiency of the hydration reaction determines the long-term stability and durability of the material. Efficient hydration reactions can generate more stable hydration products, reduce the degradation of the material in harsh environments (such as acidic or saline environments), and thus ensure its long-term anti-seepage effect on heavy metals.

[0026] The silicate and aluminate components in blast furnace slag interact with the volcanic ash active substances in lithium slag to form hydration products such as ettringite, calcium silicate hydrate (CSH) and calcium aluminosilicate hydrate (CASH). These hydration products not only provide the mechanical strength of concrete to improve the durability of solid waste-based anti-seepage materials, but also enhance the adsorption capacity of heavy metal ions due to their porous structure and high specific surface area; while the lithium, beryllium and thallium ions in lithium slag can react with the silicon and aluminum components in blast furnace slag to form hydration products with specific structures, which may have better adsorption performance and durability. For example, thallium ions participate in the formation of ettringite to form the sulfate form of thallium. At this time, the monovalent form of thallium has the properties of alkali metals, which can stabilize the crystal structure by supplementing the charge and form covalent bonds with aluminum-oxygen tetrahedrons, significantly improving the adsorption performance and durability of the material.

[0027] Through these interaction mechanisms, solid waste-based anti-seepage barrier materials can effectively adsorb and fix heavy metal ions in lithium slag landfills while improving anti-seepage performance, thereby reducing the impact on the environment.

[0028] In the present application, each material raw material must be within a limited range, otherwise it will affect the heavy metal anti-seepage effect. The factors affecting the anti-seepage effect include the adsorption of heavy metal ions and the durability of the material. Among the various components, if there is too much coal gangue, the strength of the material may be reduced, thereby reducing the durability of the solid waste-based anti-seepage material. The reason is that the activity of coal gangue is relatively low, and excessive use may lead to insufficient hydration reaction; too much lithium slag will increase the alkalinity of the material. Too high alkalinity may damage the structure of the material and reduce durability. At the same time, too much lithium slag will lead to too many lithium ions, which will then react adversely with other components and affect the stability of the material, but too little lithium slag will reduce the activity of volcanic ash and reduce the mechanical properties and durability of the material; too much blast furnace slag will affect the formation of hydration products due to the high silicon-aluminum ratio, resulting in reduced strength, while too little will reduce the hydraulic activity and affect the strength and stability of the material; too much alkali slag will increase the alkalinity of the material, which may cause corrosion and structural damage to the material, affecting the workability and machinability of the material, while too little will not be enough to provide the necessary alkaline environment, affecting the hydration reaction of the material and the adsorption of heavy metals.

[0029] In some embodiments, the modifier includes a mixture of polyferric sulfate and nano-silicon dioxide in a mass ratio of 1:(1-2).

[0030] In the present application, the addition of a modifier will produce modified calcium silicate hydrate (CSH) and modified calcium aluminosilicate hydrate (CASH).

[0031] The modifier (polyferric sulfate (PFS) and / or nano-silica (n-SiO2)) of the present application can chemically react with the surface of CSH to form a new layer of compounds, which can increase the surface roughness and porosity of CSH, thereby improving its adsorption performance. At the same time, the modifier can promote the polymerization reaction of CSH to form more CSH gels with higher polymerization degree, and these gels have better mechanical properties and durability.

[0032] In short, the advantages of modified calcium silicate hydrate (CSH) are as follows: 1. Enhanced mechanical properties of materials: The modified CSH has a denser structure, which improves the compressive strength and durability of the material. 2. Enhanced adsorption properties of materials: The surface of the modified CSH becomes rougher and more porous, providing more adsorption sites and enhancing the adsorption capacity of heavy metal ions.

[0033] The modifier (polyferric sulfate (PFS) and / or nano-silica (n-SiO2)) of the present application can form new chemical bonds with the silicon and aluminum components in CASH, and these chemical bonds can enhance the structural stability and durability of CASH. At the same time, the modifier fills the pores of CASH and reduces the porosity, thereby improving the density and impermeability of the material.

[0034] In short, the advantages of modified calcium aluminosilicate hydrate (CASH) are as follows: 1. Improve the durability of the material: The modified CASH has better impermeability and chemical corrosion resistance, which improves the durability of the material. 2. Enhance the stability of the material: The modified CASH can remain stable under different environmental conditions, reducing the degradation of material performance caused by environmental changes.

[0035] The modifier of the present application can react with the surface covalent bond structure of hydration products such as hydrated calcium silicate in solid waste-based materials, change its surface properties, and enhance the adsorption performance and durability of the material. The addition of the modifier can improve the material's impermeability and chemical corrosion resistance, thereby improving the overall performance of the anti-seepage barrier. The specific mechanism is as follows:

[0036] Polyferric sulfate (PFS) is a commonly used inorganic polymer flocculant, which can not only modify calcium silicate hydrate, but also react with the silicon and aluminum components in blast furnace slag and the active components in lithium slag.

[0037] The modification effects include: PFS can react with calcium silicate hydrate to generate more hydration products, increase the density and strength of the material, and the addition of PFS can increase the specific surface area of ​​ettringite, provide more active sites, and thus enhance its adsorption capacity for heavy metal ions and other harmful substances; the iron ions in PFS can react chemically with the aluminates and sulfates in ettringite to form stable iron aluminates and iron sulfates. These newly formed compounds can change the crystal structure of ettringite, making it more compact and stable. The iron ions can act as a catalyst for the growth of ettringite crystals, promoting the growth and development of ettringite crystals, thereby improving the strength and durability of the system. Iron ions form insoluble complexes with heavy metal ions, further reducing the mobility of heavy metals. PFS can form more hydrated calcium aluminosilicate with the silicon and aluminum components in blast furnace slag, improving the material's impermeability and durability.

[0038] The modification mechanism is as follows: PFS modifies calcium silicate hydrate. The iron ions in PFS can act as a catalyst to promote the polymerization reaction of calcium silicate hydrate and form more CSH gel, thereby improving the density and strength of the material; PFS modifies blast furnace slag. PFS can react with silicates and aluminates in blast furnace slag to generate more calcium silicate aluminate hydrate. These hydration products have a good filling effect and can improve the density and durability of the material; PFS modifies lithium slag. PFS can react with the active ingredients in lithium slag to form hydration products with good adsorption properties, thereby improving the material's adsorption capacity for heavy metal ions.

[0039] Nano-silicon dioxide (n-SiO2) is a nanomaterial with high specific surface area and activity, which can modify both coal gangue and blast furnace slag.

[0040] The modification effects include: improving the density and strength of the material. The nanoparticles of n-SiO2 can fill the tiny pores in the calcium sulfoxide and reduce the porosity, thereby improving the density and impermeability of the material. This filling effect can effectively prevent the penetration and migration of harmful substances. At the same time, the high activity of the nanoparticles can promote the hydration reaction, increase the hydration products, and improve the strength of the material; enhancing the adsorption performance. The high specific surface area of ​​n-SiO2 provides more adsorption sites and enhances the adsorption capacity of heavy metal ions; improving durability. n-SiO2 can form more hydrated calcium aluminosilicate with the silicon and aluminum components in the blast furnace slag, thereby improving the impermeability and durability of the material.

[0041] The modification mechanism is as follows: for the modification of coal gangue, n-SiO2 can form chemical bonds with the active components in the coal gangue, improve the activity of the coal gangue, and promote the hydration reaction; for the modification of blast furnace slag, n-SiO2 can react with silicates and aluminates in the blast furnace slag to generate more hydrated calcium aluminosilicate, and these hydration products can improve the density and durability of the material. By using these multifunctional modifiers, not only can the performance of solid waste-based anti-seepage barrier materials be improved, but also the versatility of the materials can be increased, so that they can play a greater role in environmental protection and resource utilization.

[0042] At the same time, the modifier not only acts on CSH and CASH, but also interacts with raw materials such as coal gangue, blast furnace slag, alkali slag and lithium slag to produce a synergistic effect and further improve material performance.

[0043] In some embodiments, the particle size of the coal gangue is 0.18-0.25 mm, the particle size of the blast furnace slag is 10-75 μm, the particle size of the alkali slag is 0.15-0.25 mm, and the particle size of the lithium slag is 37-74 μm.

[0044] The particle size distribution of the gangue, blast furnace slag, alkali slag and lithium slag of the present application is controlled within a specific range to optimize the density and pore structure of the material, and further improve the durability of the material and the adsorption of heavy metal ions. Specifically, the gangue is within the particle size range, which is conducive to maintaining a high activity and adsorption performance; the blast furnace slag is within the particle size range to ensure good hydraulic activity. The material with high hydraulic activity can form a denser hydration product structure, close the pores in the material, thereby preventing the migration of moisture and harmful substances (such as metal ions), which not only helps to solidify heavy metals and reduce their diffusion in the environment, but also improves the material's impermeability and anti-seepage effect; the alkali slag is within the particle size range, which is conducive to providing an alkaline environment; the lithium slag is within the particle size range to maintain a high volcanic ash activity. By controlling the particle size distribution, the uniformity and density of the material can be improved, the porosity can be reduced, and the material's impermeability and durability can be improved. The specific particle size distribution can also promote the uniformity of the hydration reaction and improve the uniformity and stability of the hydration product.

[0045] In some embodiments, in the blast furnace slag, the molar ratio of calcium to silicon is ≤0.6, the molar ratio of aluminum to silicon is ≥0.15, and the molar ratio of calcium to the sum of silicon and aluminum is ≤1.3.

[0046] In the present application, the molar ratio of calcium to silicon is ≤0.6, so that the coexistence of CSH and CASH is achieved, which is beneficial for subsequent modification.

[0047] The present application provides a method for preparing a solid waste-based anti-seepage material, comprising the following steps: mixing coal gangue, lithium slag, alkali slag, and blast furnace slag that have been ball-milled and dried according to parts by mass, and then adding water, heating and stirring to obtain a mixture; adding a modifier to the mixture, carrying out a modification reaction, and obtaining the solid waste-based anti-seepage material.

[0048] In this application, the core solid waste-based barrier anti-seepage material mixture is coal gangue, blast furnace slag, lithium slag, and alkaline slag, which can produce hydrated calcium silicate and hydrated calcium aluminosilicate, which can provide mechanical strength for the cushion layer to improve the durability of the material on the one hand, and can adsorb and block the infiltration of heavy metal ions in the lithium slag yard on the other hand. The modifier of this application produces a covalent bond structure on the surface of the hydration products such as modified hydrated calcium silicate, enhances the adsorption performance of the material inside for the heavy metal infiltration liquid in the lithium slag yard, and reduces the migration risk of heavy metals.

[0049] In some embodiments, the heating and stirring process includes a first heating reaction and a second heating reaction; the final temperature of the first heating reaction is 60-70°C, the duration is 18-30h, and the heating rate is 1-2°C / h; the final temperature of the second heating reaction is 90-100°C, the duration is 6-12h, and the heating rate is 4-5°C / h.

[0050] In this embodiment, the temperature is raised in two stages, first slowly to 60-70°C to fully mix the raw materials, and then quickly raised to 90-100°C, which is conducive to the full formation and subsequent rapid heating of hydration products such as ettringite, calcium silicate hydrate (CSH) and calcium aluminosilicate hydrate (CASH).

[0051] In some embodiments, the pH value of the heated stirring is 10-12.

[0052] In this application, pH value has an important influence on the formation and stability of hydration products. By accurately controlling the pH value, the formation of specific hydration products can be promoted, and the mechanical properties and durability of the material can be improved. At the same time, the appropriate pH value can enhance the adsorption capacity of the material for heavy metal ions and reduce the migration of heavy metals.

[0053] In some embodiments, the pH of the modification reaction is 5-7.

[0054] In the present application, the pH of the modification reaction is within a limited range, which can achieve the coexistence and synergistic effect of polyferric sulfate and nano-silicon dioxide.

[0055] The present application provides an application of a solid waste-based anti-seepage material as a geopolymer, and the application method includes: mixing the solid waste-based anti-seepage material, hydrotalcite, and a piezoelectric catalyst and then landfilling.

[0056] Example 1

[0057] A solid waste-based anti-seepage material comprises the following components in mass parts: 40 parts of coal gangue, 20 parts of blast furnace slag, 25 parts of lithium slag, 15 parts of alkali slag, and 5 parts of modifier; the modifier comprises a mixture of polyferric sulfate and nano-silicon dioxide in a mass ratio of 1:1; the particle size of the coal gangue is 0.18 mm, the particle size of the blast furnace slag is 10 μm, the particle size of the alkali slag is 0.15 mm, and the particle size of the lithium slag is 37 μm; in the blast furnace slag, the molar ratio of calcium to silicon is 0.6, the molar ratio of aluminum to silicon is 0.15, and the molar ratio of calcium to the sum of silicon and aluminum is 1.3.

[0058] A preparation method of a solid waste-based anti-seepage material comprises the following steps: mixing coal gangue, lithium slag, alkali slag and blast furnace slag after ball milling and drying by weight, and then adding water to obtain a slurry with a solid content of 0.3%, followed by heating and stirring, wherein the heating and stirring process comprises a first heating reaction and a second heating reaction, wherein the final temperature of the first heating reaction is 60°C, the duration is 18 hours, and the heating rate is 1°C / h; the final temperature of the second heating reaction is 100°C, the duration is 12 hours, the heating rate is 5°C / h, and the pH value of the heating and stirring is 10, thereby obtaining a mixture; and adding a modifier to the mixture to carry out a modification reaction, wherein the pH value of the modification reaction is 5, thereby obtaining the solid waste-based anti-seepage material.

[0059] Embodiment 2-5

[0060] A solid waste-based anti-seepage material, other contents are the same as those of Example 1, except that the components are formulated according to Table 1.

[0061] Table 1: Composition of components in Examples 1-5 (parts by mass)

[0062]

[0063] Example 6

[0064] A solid waste-based anti-seepage material, other contents are the same as those in Example 1, except that the pH value of the heated stirring is 9.

[0065] Example 7

[0066] A solid waste-based anti-seepage material, other contents are the same as those in Example 1, except that the pH value of the modification reaction is 10.

[0067] Example 8

[0068] A solid waste-based anti-seepage material, other contents are the same as those of Example 1, except that the modifier does not include polyferric sulfate.

[0069] Example 9

[0070] A solid waste-based anti-seepage material, other contents are the same as those of Example 1, except that the modifier does not include nano-silicon dioxide.

[0071] Example 10

[0072] A solid waste-based anti-seepage material is used as a geopolymer, and the application method comprises: mixing the solid waste-based anti-seepage material, hydrotalcite and a piezoelectric catalyst in a ratio of 100:5:10 and then landfilling.

[0073] Comparative Examples 1-5

[0074] A solid waste-based anti-seepage material, other contents are the same as those in Example 1, except that the components are formulated according to Table 2.

[0075] Table 2 Component formulation of comparative examples 1-5 (parts by mass)

[0076] Coal Gangue Lithium slag Blast furnace slag Alkali residue Modifier Comparative Example 1 0 0 0 0 5 Comparative Example 2 40 20 25 15 0 Comparative Example 3 35 20 25 15 0 Comparative Example 4 40 15 25 15 0 Comparative Example 5 40 20 20 15 0

[0077] Comparative Example 6

[0078] A solid waste-based anti-seepage material, other contents are the same as those of Example 1, except that alkali residue is not included.

[0079] Comparative Example 7

[0080] A solid waste-based anti-seepage material, the other contents are the same as those of Example 1, except that the final temperature of the heating and stirring process is 60°C, the duration is 18 hours, and the heating rate is 1°C / h.

[0081] Comparative Example 8

[0082] A solid waste-based anti-seepage material, the other contents are the same as those of Example 1, except that the final temperature of the heating and stirring process is 100°C, the duration is 12 hours, and the heating rate is 5°C / h.

[0083] Test and Evaluation

[0084] The electron microscope images of the solid waste-based cushion layer obtained in Example 1 and Comparative Example 9 are as follows: Figure 1 As shown, Figure 1 (a) is the solid waste-based cushion layer before modification (Comparative Example 1), which has more internal pores, less hydration products, and no dense structure is formed, so harmful ions can easily penetrate the cushion layer and enter the underground; Figure 1 (b) is the modified solid waste-based cushion layer (Example 1), in which the hydration products increase, and the structures of the hydration products are intertwined to improve the mechanical properties and durability. The dense structure formed inside can effectively prevent the penetration of harmful ions.

[0085] The leachate of lithium slag, beryllium and thallium in each embodiment and comparative example was tested according to the method of "Hazardous Waste Identification Standard Leaching Toxicity Identification GB 5085.3-2007" and "Solid Waste Leaching Toxicity Leaching Method Sulfuric Acid Nitric Acid Method HJ / T 299-2007", and the experimental results are shown in Table 3. The lower the percolation concentration, the better the anti-seepage effect. The percolation results after 180 days are shown in Table 4, which reflects the durability of the cushion layer.

[0086] Table 3 Heavy metal percolation results

[0087]

[0088]

[0089] Table 4 Durability test results

[0090]

[0091]

[0092] This application can significantly reduce production costs by optimizing the proportion of solid waste-based cementitious materials and realizing full component optimization control technology, making the production cost of solid waste-based cementitious materials 50% lower than that of ordinary Portland cement, and reducing carbon emissions by 90%. The application of solid waste-based anti-seepage layers can not only prevent the problem of heavy metal seepage in the storage yard, but also absorb industrial solid waste, reduce the cost of using anti-seepage cushion layers in lithium slag storage yards, and achieve the purpose of using waste to treat harm.

[0093] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A solid waste-based anti-seepage material, characterized in that: The invention comprises the following components in parts by weight: 40-45 parts of coal gangue, 20-30 parts of blast furnace slag, 20-25 parts of lithium slag, 10-20 parts of alkali slag and 5-10 parts of modifier.

2. The solid waste-based anti-seepage material according to claim 1, characterized in that: The modifier comprises a mixture of polyferric sulfate and nano silicon dioxide in a mass ratio of 1:(1-2).

3. The solid waste-based anti-seepage material according to claim 1, characterized in that: The particle size of the coal gangue is 0.18-0.25 mm, the particle size of the blast furnace slag is 10-75 μm, the particle size of the alkali slag is 0.15-0.25 mm, and the particle size of the lithium slag is 37-74 μm.

4. The solid waste-based anti-seepage material according to claim 1, characterized in that: In the blast furnace slag, the molar ratio of calcium to silicon is ≤0.6, the molar ratio of aluminum to silicon is ≥0.15, and the molar ratio of calcium to the sum of silicon and aluminum is ≤1.

3.

5. A method for preparing the solid waste-based anti-seepage material according to any one of claims 1 to 4, characterized in that: The following steps are involved: The coal gangue, lithium slag, alkali slag and blast furnace slag that have been ball-milled and dried are mixed according to mass parts, and then water is added, heated and stirred to obtain a mixture; a modifier is added to the mixture to carry out a modification reaction to obtain the solid waste-based anti-seepage material.

6. The preparation method according to claim 5, characterized in that: The heating and stirring process includes a first heating reaction and a second heating reaction; the final temperature of the first heating reaction is 60-70°C, the duration is 18-30h, and the heating rate is 1-2°C / h; the final temperature of the second heating reaction is 90-100°C, the duration is 6-12h, and the heating rate is 4-5°C / h.

7. The preparation method according to claim 5, characterized in that: The pH value of the heating and stirring is 10-12.

8. The preparation method according to claim 5, characterized in that: The pH value of the modification reaction is 5-7.

9. Use of the solid waste-based anti-seepage material according to any one of claims 1 to 4 as a geopolymer.

10. The use according to claim 9, characterized in that: The application method includes mixing the solid waste-based anti-seepage material, hydrotalcite and piezoelectric catalyst and then landfilling.

Citation Information

Cited By

  • Heavy metal curing agent and method for curing and repairing heavy metal contaminated soil

    CN122168299A